Establishment of the Council of Europe’s activities on the protection of human rights and freedoms (Bulletin of Kharkiv National University of Internal Affairs, 2025)
The article is devoted to the process of the establishment of the Council of Europe's activities in the field of human rights and freedoms protection. The historical context of the creation of this organisation after the Second World War is analysed, in particular, the prerequisites that led to international cooperation of European countries on this issue.The founding of the Council of Europe in 1949, its basic principles enshrined in the Charter, as well as the stages of development of the organisation's human rights mechanism are considered. Considerable attention is paid to the adoption of the European Convention on Human Rights in 1950, its structure, fundamental rights and freedoms guaranteed by the document, as well as further amendments and additions adopted in the form of annexes. The author analyses the evolution of the human rights mechanism, including the adoption of additional protocols that expanded the list of guaranteed rights and improved the procedures for their protection.The process of reforming the system of human rights monitoring, which culminated in the adoption of Protocol No. 11, which established the permanent European Court of Human Rights, providing it with supranational status and compulsory jurisdiction, is considered. The role of the European Court of Human Rights and the European Commission of Human Rights, their evolution and reforms, in particular the 1998 reform that led to the creation of a single permanent Court, are examined.Particular attention is paid to the analysis of the system of control over the observance of human rights within the Council of Europe, its impact on the legal systems of member states and the development of European precedent. The study concludes that the activities of the Council of Europe have become a key element in the formation of the human rights protection system, and the European Convention on Human Rights has established international bodies for monitoring the observance of these rights and fundamental freedoms and empowered them to make decisions binding on member States, which has made it possible to achieve real restoration of human rights and freedoms in case of their violation. It is emphasised that the activities of the Council of Europe and its human rights mechanism have contributed to improving the level of human rights protection in Europe. The European Convention on Human Rights and its mechanisms have become an effective tool for ensuring democratic standards and the rule of law in the member states of the Council of Europe.
Keywords: Council of Europe; human rights and freedoms; Convention for the Protection of Human Rights and Fundamental Freedoms; Charter of the Council of Europe; European Commission of Human Rights; European Court of Justice; Additional Protocols to the Convention.